PRESERVATIVE USING CRUSHING STRENGTH (2009)
A study was carried out to determine the efficiency of wood energy production in Akinyele Local Government of Oyo State. Ten fuelwood and five charcoal wood species were selected as samples using availability as criterion. Energy parameters including moisture, ash and energy contents, and density of the samples were determined. The earth kiln system of charcoal production was used 10 determine the efficiency of the charcoal production method. Data analysis was carried out using a combination of t-tests and descriptive statistical methods. Results showed that the moisture contents ranged between 10.6 and 32.45% for the fuelwood species and 5.2 and 7.7% for charcoal. The ash contents ranged between 1.0 and 6.0% for fuelwood species and 10 and 5.0% for charcoal. Energy contents for fuel wood range between 15.79 and 28.58 MJ/kg and between 2.51 and 6.82 MJ/kg for charcoal respectively. Specific gravity for fuelwood species ranged between 0.53 for Markhamia and 0.89 for Funtumia and between 0.46 for Parkia and 0.63 for Butyreospermum for charcoals species. Outputs from the earth kiln method were found to be about 21.01% which implies that at least one kilogramme of charcoal is produced from five kilogramme of wood.